Antimicrobial and Phytochemistry study of Liparis resupinata Ridl. from Mount Gumitir, East Java, Indonesia - Ulum, Fuad Bahrul; Setyati, Dwi; Rizqoni, Moh. Ikmal Alfi; Su'udi, Mukhamad (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2023)
Liparis resupinata Ridl. is one of the abundant epiphytic orchids in the Mount Gumitir, Jember Regency with potency for phytopharmacy study. Our study focused on the observation of the species for their antimicrobial and metabolite profiles. This study used Gram-positive and Gram-negative bacteria, i.e., S. aureus, S. typhi, and E. coli with an agar diffusion method for antibacterial activity test. The metabolite profile was generated through GC-MS. The methanolic extract of the leaves of L. resupinata showed positive antibacterial activity. The GC-MS data analysis suggested the presence of antimicrobial substances e.g., (-)-loliolide, nonanoic acid, 1,2-ethanediamine, and hydroxy dimethyl furanone.